Medical Informatics Training at Yale University School of Medicine - Miller, P.L.; Shiffman, R.N.; Silverstein, S.; Frawley, S.J.; Nadkarni, P.M. (Yearbook of Medical Informatics, 1996)
The Yale Center for Medical Informatics has offered Medical Informatics training since 1986. The paper describes the overall structure of the training program, focusing primarily on the postdoctoral fellowship, a major component of which involves an independent project which the fellow carries out under faculty supervision. The paper outlines a number of areas in which such projects have been performed, describes the previous backgrounds and post-training career directions of the trainees, and discusses certain observations based on our experience with the program.